MR relaxometry and 1H MR spectroscopy for the determination of iron and metabolite concentrations in PKAN patients - Hájek, Milan; Adamovicová, Miriam; Herynek, Vít; Skoch, Antonín; Jírů, Filip; Krepelová, Anna; Dezortová, Monika (European radiology, 2005)
The influence of iron deposits on T2 values and the content of metabolites in the brain of three patients with DNA proved pantothenate kinase-associated neurodegeneration (PKAN, formerly Hallervorden-Spatz syndrome) was studied. An eye-of-the-tiger sign, a typical MR finding for PKAN, was observed in two patients with the same mutation. A hypointensive lesion in a whole globus pallidus was observed in the third patient with the additional mutation. T2 values in the globus pallidus of the patients were about 40% shorter than in controls (71/48 ms in controls vs. patients), which corresponds to the increase of Fe concentration based on the ferritin basis from 17 mg for controls to 48 mg (100 g wet brain weight) in PKAN patients. 1H MR spectroscopy (MRS) has mainly been used to describe neuronal damage represented by decreased NAA (6.4 mmol vs. 9 mmol) and Cr/PCr (7.0 mmol vs. 9.8 mmol) concentrations in the basal ganglia region of the patient group to controls; MRS is much more case-sensitive and describes individual development of the disease as demonstrated in the difference between the spectra of typical PKAN patients (1, 2), and the patient (3) with atypical PKAN development. Any significant changes of metabolite concentration with the exception glutamine, glutamate and GABA were found in the white matter.
Keywords: Hallervordenův-Spatzův syndrom; Adolescent; Iron; Magnetic Resonance Imaging; Male; Magnetic Resonance Spectroscopy; lidé; Humans; Mutation; neparametrická statistika; magnetická rezonanční spektroskopie; Statistics, Nonparametric; mužské pohlaví; železo; ženské pohlaví; mladiství; mutace; Female; Pantothenate Kinase-Associated Neurodegeneration; magnetická rezonanční tomografie